2020
DOI: 10.3390/ani10122359
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Evolution of the Sweet Taste Receptor of Primates Adapted to Harsh Environments

Abstract: Taste perception is an essential function that provides valuable dietary and sensory information, which is crucial for the survival of animals. Studies into the evolution of the sweet taste receptor gene (TAS1R2) are scarce, especially for Bornean endemic primates such as Nasalis larvatus (proboscis monkey), Pongo pygmaeus (Bornean orangutan), and Hylobates muelleri (Muller’s Bornean gibbon). Primates are the perfect taxa to study as they are diverse dietary feeders, comprising specialist folivores, frugivores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
(104 reference statements)
2
1
0
Order By: Relevance
“…In our study, the expression of OCT4 in 5% CM and co‐culture groups was higher than control ( p < .5) while, no significant difference was observed between treatment groups (Figure 3). The results of our study were consistent with the results of some studies (Kim et al., 2011; Sakurai et al., 2016; Tamrin et al., 2020). In pre‐implantation bovine embryos OCT4 and CDX2 are essential for early embryonic development and their expression is involved in the differentiation of ICM and TE lineage in the embryos (Sakurai et al., 2016).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study, the expression of OCT4 in 5% CM and co‐culture groups was higher than control ( p < .5) while, no significant difference was observed between treatment groups (Figure 3). The results of our study were consistent with the results of some studies (Kim et al., 2011; Sakurai et al., 2016; Tamrin et al., 2020). In pre‐implantation bovine embryos OCT4 and CDX2 are essential for early embryonic development and their expression is involved in the differentiation of ICM and TE lineage in the embryos (Sakurai et al., 2016).…”
Section: Discussionsupporting
confidence: 94%
“…It has been suggested that it has a potential role in placental development and the maternal‐foetal crosstalk and its expression is a sign of high quality embryo. Its expression was higher in blastocysts of 5% CM group that control group (Figure 3), which was consistent with some reports (El‐Sayed et al., 2006; Li et al., 2016; Tamrin et al., 2020). Study in bovine embryos has shown that blastocysts with higher expression of pregnancy‐related genes ( PLAC8 ) are more likely to give birth to calves (El‐Sayed et al., 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation